2015
DOI: 10.1016/j.psychres.2015.08.004
|View full text |Cite
|
Sign up to set email alerts
|

The association between childhood trauma and facial emotion recognition in adults with bipolar disorder

Abstract: Many patients with bipolar disorder (BD) have difficulties in facial emotion recognition, which may also be impaired in maltreated children and in subjects who have a positive history of childhood traumatic experiences. Childhood trauma is reported with a high prevalence in BD and it is considered a risk factor for the disorder. As the relationship between facial emotion recognition and childhood trauma in BD has not yet been directly investigated, in this study we examined whether the presence of a childhood … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
43
3
2

Year Published

2016
2016
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 49 publications
(51 citation statements)
references
References 60 publications
3
43
3
2
Order By: Relevance
“…Likewise, these cognitive domains have been widely reported to be affected in other studies in this area . Nevertheless, we were not able to fully replicate findings reported by Russo and colleagues, who observed that bipolar patients with a history of CT presented more difficulties in emotional facial recognition. We only observed a trend concerning an association between social cognition and higher scores on the physical neglect subscale.…”
Section: Discussioncontrasting
confidence: 86%
“…Likewise, these cognitive domains have been widely reported to be affected in other studies in this area . Nevertheless, we were not able to fully replicate findings reported by Russo and colleagues, who observed that bipolar patients with a history of CT presented more difficulties in emotional facial recognition. We only observed a trend concerning an association between social cognition and higher scores on the physical neglect subscale.…”
Section: Discussioncontrasting
confidence: 86%
“…While sexual abuse alone has been reported as a significant risk factor for psychotic symptoms (Cutajar et al ., ), no particular type of trauma has been consistently implicated as a stronger predictor of psychotic symptoms relative to any other (Varese et al ., ). Early life adversity has also been shown to directly impact cognitive and clinical features associated with psychosis (Barch & Sheffield, ), including higher cognitive functions, such as executive functions, working memory, attention (Hart & Rubia, ) and recognition and processing of emotional material (Delvecchio, Sugranyes, & Frangou, ; Russo et al ., ). Additionally, trauma exposure has been associated with schizotypal personality features in non‐clinical populations (Sheinbaum, Kwapil, & Barrantes‐Vidal, ; Velikonja, Fisher, Mason, & Johnson, ).…”
Section: Introductionmentioning
confidence: 97%
“…With respect to facial emotion processing, contradictory evidence has been reported, showing either difficulties in discriminating emotions (Hart & Rubia, ), or no impact of trauma on facial emotion processing in healthy individuals (Germine et al ., ). In addition, deficits in facial emotion (anger) recognition have been reported in BD cases exposed to significant levels of emotional neglect (Russo et al ., ). Several neuroimaging studies also show trauma‐related amygdala hyper‐reactivity during negative facial emotion processing in patients with depression and/or anxiety disorders (van Harmelen et al ., ), and in healthy controls (Dannlowski et al ., ), suggesting that neurocognitive systems for social cognition are indeed associated with trauma exposure.…”
Section: Introductionmentioning
confidence: 97%
See 1 more Smart Citation
“…On the contrary to healthy populations, certain populations with abnormal impulsivity may respond more selectively to emotional saliency that is potentially related to abnormal behaviors and enhance sensory-perceptual change detection (22). Besides, it was known that the rate of abuse is higher in psychopathologies that goes on with insecure attachment, emotion recognition deficits and impulsivity, such as attention deficit hyperactivity disorder (ADHD), eating disorders, bipolar affective disorder (23)(24)(25)(26), than that of healthy people.…”
Section: Introductionmentioning
confidence: 99%